Pengaruh Alokasi Pajak Antar Periode, Return On Asset Dan Karakteristik Komite Audit Terhadap Kualitas Laba Pada Perusahaan Jasa Sektor Infrastruktur, Utilitas Dan Transportasi Yang Terdaftar Di Bursa Efek Indonesia - Trisna Novrianti Pratiwi; Muhammad Salman; Nasrul Kahfi Lubis (LPPM Universitas Labuhanbatu, 2022)
This study aims to determine the effect of tax allocation between periods, return on assets, and the characteristics of the audit Committee on the quality of earnings in the infrastructure, utilities and transportation sector service companies listed on the Indonesia Stock Exchange. The population in this study is infrastructure, utilities and transportation sector service companies listed on the Indonesia Stock Exchange in the period 2016-2020. Samples in this study were selected using purposive sampling method with the results of research samples as many as 18 companies. The method used in this study is multiple linear regression analysis using the application of SPSS (Statistical Package for Social Sciences) version 16. The results of this study indicate that simultaneous tax allocation between periods, Return on assets, and the characteristics of the Audit Committee have a significant effect on the quality of profit. Partially, the allocation of taxes between periods and Return on assets does not significantly affect the quality of profits. While the characteristics of the Audit Committee have a positive and significant effect on the quality of profit. Limitations in this study that researchers develop this study less than previous research. Lack of recent references and the latest theories used by researchers.